Extrapulmonary Tuberculosis in Indonesia - Audira Budiantari; Dian Handayani; Damas Andhika; Al Asyary (JUMP Health (Journal of Ultimate Public Health), 2019)
Tuberculosis is one of contagious disease that is caused by the germ of Mycobacterium class, which is Mycobacterium Tuberculosis. The transmission of the tuberculosis infection would happen if someone breathes the air containing thick saliva of the infected. When sneezes, a patient spreads out the germ into the air in form of sputum splotch. One cough could produce around 3000 sputum splotches. The method used in this research is the method of scientific papers investigation, which are two papers in search. The result of the research shows that the patient of Extrapulmonary TB mostly are in group of productive age with gender characteristics between male and female are both having same risk level.